2020
DOI: 10.3390/nu13010045
|View full text |Cite
|
Sign up to set email alerts
|

Childbearing Age Women Characteristics in Latin America. Building Evidence Bases for Early Prevention. Results from the ELANS Study

Abstract: Latin American (LA) women have been exposed to demographic and epidemiologic changes that have transformed their lifestyle, with increasing sedentary and unhealthy eating behaviors. We aimed to identify characteristics of LA women to inform public policies that would benefit these women and their future children. The Latin American Study of Nutrition and Health (ELANS) is a multicenter cross-sectional study of representative samples in eight Latin American countries (n = 9218) with a standardized protocol to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The education on and promotion of health, including dietary intake that meets nutrient and micronutrient needs, with the use of supplementation and food fortification if necessary, may constitute policies to improve nutritional deficiencies in general [ 26 , 58 , 76 ]. However, the gaps in knowledge about calcium and vitamin D deficiency and associated factors in Brazilian women are diverse, making it impossible to establish public policies due to insufficient evidence, particularly for different ethnic/racial groups [ 34 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The education on and promotion of health, including dietary intake that meets nutrient and micronutrient needs, with the use of supplementation and food fortification if necessary, may constitute policies to improve nutritional deficiencies in general [ 26 , 58 , 76 ]. However, the gaps in knowledge about calcium and vitamin D deficiency and associated factors in Brazilian women are diverse, making it impossible to establish public policies due to insufficient evidence, particularly for different ethnic/racial groups [ 34 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypocalcemia develops when the calcium concentration is below 3 mg/dL (0.75 mmol/L) [ 25 ]. An observational study conducted in Latin America found that a high number of women of childbearing age have an inadequate calcium intake, especially in Peru (97.74%), Costa Rica (95.88%), Brazil (95.16%), and Chile (93.23%) [ 26 ]. Calcium deficiencies trigger disorders ranging from mild (such as perioral paresthesia) to severe (such as cardiac arrhythmias) [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other states, several studies identified the low frequency of dairy consumption. The gap between actual consumption versus the one recommended by the WHO and other food safety policies was evident on those studies (GBD 2017 Diet Collaborators, 2019) (Herrera-Cuenca et al, 2020). However, Pertuz-Cruz et al noticed that during the COVID-19 pandemic, Colombians increased the frequency of consumption of dairy products (Pertuz-Cruz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Underweight was established at BMI for age < −2 SD, normal weight between −2 SD ≤ BMI for age ≤ 1 SD, overweight between 1 SD ≤ BMI for age ≤ 2 SD, and obese BMI for age > 2 SD. The WHO growth charts are regularly used in the Latin American countries; thus, it was selected as appropriate for this and the other ELANS studies ( 29 ). For adults (older than 19 years old), BMI was categorized as underweight (<18.5 kg/m 2 ), normal weight (18.5–24.9 kg/m 2 ), overweight (25–29.9 kg/m 2 ), and obese (≥30.0 kg/m 2 ) ( 30 ).…”
Section: Methodsmentioning
confidence: 99%